The case of the rVSV-ZEBOV vaccine: tragic lessons from a delayed solution to the 2014 Ebola Outbreak - Galindez, Julia; Ling, Yifan; Sanchez, Diana; Wilson, Lucy (McGill Journal of Global Health, 2018)
Abstract unavailable.